Shrinkage cracking and strength deterioration of red clay under cyclic drying and wetting - Yanhua Xie (Elsevier, 2022)
Taking the red clay from Guilin, China as the object, this paper prepares red clay samples with different initial water contents, extracts the crack parameters from the images on the samples under cyclic drying and wetting through image processing, and analyzes the laws of crack development. In addition, parallel red clay samples were subject to shrinkage tests and direct shear tests under the same cyclic drying and wetting. Based on the test results, the authors discussed the laws of shrinkage deformaiton and strength change for the samples under cyclic drying and wetting, and examined the relationship between cracking, shrinkage properties, and strength detiroation of the red clay. The results show that: (1) With the growing crack rate, the volume shrinkage ratio constantly declined; the area shrinkage ratio was generally decreasing, but the decrement was not obvious in local places (in some places, the area shrinkage ratio even increased); the shrinkage coefficient generally declined, (2) Through the five dry-wet cycles, it was learned that the cohesion and internal friction angle of red clay strength can be quantified using the crack rate. This finding lays the basis for judging soil strength based on crack rate, and solving actual engineering problems with the red clay.